Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Guru di Sekolah Menengah Kejuruan Kabupaten Bogor - Chandra S. Haratua; Repiharnita; Engkom Komalasari; Aang Muhsin; Iin Adril (Attractive : Innovative Education Journal, 2024)
This study aims to test and analyze the influence of Motivation and Work Environment on Teacher Performance in Vocational High Schools in Bogor Regency. The research method used is a quantitative method using questionnaires as a data collection tool. The population in this study consists of teachers teaching at SMK Prima Mulia and SMK An-Nur Klapanunggal. The sample number was 50 respondents, using a non-probability sampling research technique, namely saturated sampling. The results of the data analysis stated that there was an influence of motivation and work environment influence teacher performance in Vocational High Schools in Bogor Regency